Kajian Teori : Peringatan Terhadap Fitnah ( Analisis Tekstual Dari Yakobus 4:11-12 ) (International Forum of Researchers and Lecturers, 2023)
Hate speech is a term used for negative language on social media bringing someone down. Someone's envy or hatred tries to destroy other people in a way that is not good, one of which is slander. That means the person who commits slander considers himself to be above the law so he can manipulate the law for his personal gain. In fact, the writer of the letter James states that there is only one legislator, namely God, only God is able to harm someone based on His law. Humans should not play with the law, but rather become law-abiding beings. The data analysis used in this research follows the steps of grammatical analysis. It is very important to look up the meaning of each sentence to see or have an idea of what is meant in Warning Against Slander. James 4:11-12 this is one of the verses in the letter written by James, who is believed to be the brother of Jesus. The letter of James is addressed to Christians in general, containing moral, ethical, and practical advice on how to live as a believer. In this context, James emphasizes the importance of not slandering or judging fellow believers. He reminded that slandering or judging other people seemed to take on the role of a judge that only God should have. James shows that such behavior is contrary to Christ's teachings on love and forgiveness. Based on the concept above, the writer concludes that James' letter changes us, there is a risk behind slander. The risk is aimed specifically at people who are used to slander. As they say, playing with fire can get you burned. Likewise, those who play with the law will receive their own punishment from God.